Testing ground GDR: Western pharmaceutical firms conducting clinical trials behind the Iron Curtain - Erices, Rainer; Frewer, Andreas; Gumz, Antje (Journal of Medical Ethics, 2015)
Western pharmaceutical companies conducted clinical trials in the Eastern Bloc during the Cold War. Recently, media reports about alleged human experimentation provoked a wave of indignation. However, a scientific and objective account of these trials is lacking. The aim of this study was to describe and evaluate the clinical trials performed in the German Democratic Republic (GDR) based on archival material from the health system and the secret service. We found documents relating to 220 trials involving more than 14,000 patients and 68 Western companies. However, no record of patient information forms or systematic documentation regarding the provision of patient consent was discovered. There was no evidence to suggest that the trials systematically and intentionally damaged patients. The trials were conducted without the knowledge of the public. GDR legislation stipulated that patients must consent to the trials, but no evidence was found to suggest that patients were systematically informed. Documents suggest that at least some of the trials were carried out without patients having a comprehensive understanding of what the trial involved. The GDR agreed to the trials due to impending bankruptcy and Western pharmaceutical companies capitalised on this situation.
EVALuna2:5667